Quite ugly one morning - Brookmyre, Christopher, 1968- (Abacus, 1997)
Quite Ugly One Morning is the book that made Christopher Brookmyre a star in his native Britain, establishing his distinctive, scabrously humorous style and breakneck, hell-for-leather narrative pacing.The novel that won the inaugural First Blood Award for the best debut crime novel in the United Kingdom is now available in America for the first time, and comic crime writing on this side of the Atlantic may never be the same.Quite Ugly One Morning introduces Brookmyre's signature protagonist, the hard-partying, wisecracking investigative journalist Jack Parlabane, who is not afraid to bend the laws of the land (or even the laws of gravity) to get to the truth.Parlabane is nursing a horrific hangover when he stumbles across the corpse of the scion of a wealthy Edinburgh medical family.Determined to get to the bottom of the murder himself, he quickly becomes enmeshed in a wild adventure that will take him through all the strata of Edinburgh society and into some dangerous (and hysterical) situations. Laced with acerbic wit and crackling dialogue, Quite Ugly One Morning is a wickedly entertaining and vivacious thriller.